Biogeographical variation on craniomandibular morphology in pallas’s squirrel Callosciurus erythraeus (Pallas, 1779) (Rodentia: Sciuridae) in Vietnam - Duong, Vu Thuy; Son, Nguyen Truong; Hai, Bui Tuan; Tu, Ly Ngoc; Phuong, Dang Huy; Tuan, Tran Anh; Motokawa, Masaharu; Endo, Hideki; Oshida, Tatsuo (Academia Journal of Biology, 2021)
Different forest vegetations provide herbivorous small mammals with different resources, forcing adaptation since food habits depend on available resources. We expect differences in vegetation to be reflected in the size and shape of the skull and mandible as a result of potentially different feeding resources. Therefore, we analyzed the craniomandibular characteristics of Pallas’s squirrel (Callosciurus erythraeus) in Vietnam. This species commonly occurs in different vegetations in Vietnam, making it a good model for examining morphological adaptation to vegetation type. We analyzed morphologically the skulls and mandibles of 156 specimens collected from 31 localities in Vietnam from 1960 to the present. Principal component analysis showed that females occurring in the tropical lowland evergreen rain forest were clearly separated from those in other vegetations.